Virulence genes and intimin types of Shiga-toxin-producing Escherichia coli isolated from cattle and beef products in Argentina - Blanco, Miguel (2004)
A total of 153 Shiga-toxin-producing Escherichia coli (STEC) isolates from feces of cattle and beef products (hamburgers and ground beef) in Argentina were characterized in this study. PCR showed that 22 (14%) isolates carried stx1 genes, 113 (74%) possessed stx2 genes and 18 (12%) both stx1 and stx2. Intimin (eae), enterohemolysin (ehxA), and STEC autoagglutinating adhesin (saa) virulence genes were detected in 36 (24%), 70 (46%) and in 34 (22%) of the isolates, respectively. None of 34 saa-positive isolates carried the gene eae, and 31 were ehxA-positive. Fourteen (7 of serotype O26:H11 and 4 of serotype O5:H-) isolates had intimin b1, 16 isolates possessed intimin g1 (11 of serotype O145:H- and 5 of serotype O157:H7), 5 isolates had intimin type e1 (4 of serotypes O103:H- and O103:H2), and one isolate O111:H- showed intimin type q/g2. Although the 153 STEC isolates belonged to 63 different seropathotypes, only 12 accounted for 58% of isolates. Seropathotype ONT:H- stx2 (18 isolates) was the most common, followed by O171:H2 stx2 (12 isolates), etc. The majority (84%) of STEC isolates belonged to serotypes previously found in human STEC and 56% to serotypes associated with STEC isolated from patients with hemolytic uremic syndrome (HUS). Thus, this study confirms that cattle are a major reservoir of STEC pathogenic for humans. To our knowledge, this is the first study that described the presence of saa gene in STEC of serotypes O20:H19, O39:H49, O74:H28, O79:H19, O116:H21, O120:H19, O141:H7, O141:H8, O174:H21, and ONT:H21. The serotypes O120:H19 and O185:H7 were not previously reported in bovine STEC.